Webinar: Role of Women in Developing a Climate Smart Seed System in the Philippines - Bertuso, Arma; Baruah, Sampriti (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The growing importance of women in the Philippine agriculture makes it imperative that the gender perspectives are integrated in crafting a climate-smart seed system. The webinar provided a platform for discussing the role of women in developing a climate-smart seed system in the Philippines.